SmMYC2b Enhances Tanshinone Accumulation in Salvia miltiorrhiza by Activating Pathway Genes and Promoting Lateral Root Development - Zhou, Yangyun; Feng, Jingxian; Li, Qing; Huang, Doudou; Chen, Xiao; Du, Zenan; Lv, Zongyou; Xiao, Ying; Han, Yonglong; Chen, Junfeng; Chen, Wansheng (Frontiers in Plant Science, 2020)
Salvia miltiorrhiza Bunge (Lamiaceae) is an economically important medicinal plant as well as an emerging model plant. Our previous studies indicate that SmMYC2b is a positive transcription factor that can affect the biosynthesis of phenolic acids and tanshinones in S. miltiorrhiza. Moreover, MYC2s are well known to induce the development of lateral roots. As tanshinones are mainly distributed in the periderm, the promotion of lateral root development probably leads to increased accumulation of tanshinones. In this paper, we firstly discovered that SmMYC2b played a dual regulatory role in effectively enhancing the tanshinone accumulation by activating tanshinone biosynthetic pathway and promoting lateral root development. The expression levels of the previously studied pathway genes SmCPS1, SmKSL1, SmCYP76AH1, SmCYP76AH3 and SmCYP76AK1 dramatically increased. In addition, SmMYC2b was proved to exhibit a similar function as other homologs in promoting lateral root development, which increased the tanshinone produced tissue and further enhanced the biosynthesis of tanshinones. RNA-seq assays revealed that SmMYC2b-regulated genes comprised 30.6% (1901 of 6210) of JA-responsive genes, confirming that SmMYC2b played a crucial role in transcriptional regulation of JA-regulated genes. Overall, we concluded that SmMYC2b could enhance tanshinone accumulation by activating the tanshinone biosynthetic pathway and promoting lateral root development. Our study provides an effective approach to enhance the production of desired tanshinones and enriches our knowledge of the related regulatory network.